HYDROTHERMAL CIRCULATION THROUGH MID-OCEAN RIDGE FLANKS: FLUXES OF HEAT AND MAGNESIUM - Mottl M.J.; Wheat C.G. (My University, 1994)
Thermally driven convection of seawater occurs through oceanic crust of all ages, at the seafloor spreading axis, on mid-ocean ridge flanks, and in the ocean basins. At the ridge axis and on the flanks, circulating seawater produces a major chemical exchange between the oceans and the crust. Based on heat budget constraints and the composition of hot springs, between 10 and 40% of the river flux of Mg can be taken up during high-temperature alteration of the basaltic crust along the ridge axis. Most of the hydrothermal heat loss, however, occurs on the mid-ocean ridge flanks, where the temperatures are lower and the seawater flux correspondingly larger. The estimated heat loss on the flanks is so large that upwelling must occur over a large fraction (5–30%) of the seafloor less than 65 Ma in age, if temperatures are < 20°C and seepage velocities are on the order of 10 to 100 cm/y. The circulating seawater needs to lose on average less than 1–2% of its Mg content in order to solve the Mg mass balance for the oceans.